Influences of different phytobiotic supplementations on growth performance, health performance and telomere length expression of broiler chickens - Abu Kassim, Nafeesa (2022)
Antibiotic resistance in poultry is detrimental to human health mainly due to the transmission of harmful antibiotic residuals from food-producing animals to consumers. Owing to public pressure, antibiotics for instance avoparcin, chloramphenicol, nitrofurans, teicoplanin, vancomysin and norfloxacin are banned in Malaysia. It is critically important to discover a safer alternative replacer for antibiotics such as phytobiotic as natural compounds that possess antibiotic properties due to their pharmacological active compound that may improve growth performance, improve microbial properties, and immunological response in poultry. The primary isssue here is a gap of knowladege on phytobiotic utilization in enhancing poultry growth and health performance. Therefore, this study intends to determine the effect of three different phytobiotic supplementations on growth performance, health performance, telomere length expression of broiler chickens. A total of 300 day-old male Ross 308 was randomly assigned to six different dietary treatments. There were five replications of each dietary treatment, with ten broilers in each replication. The dietary treatments include T1(negative control) commercial feed without antibiotic, T2(positive control) commercial feed added with 100mg/kg oxytetracycline, T3(25mg/kg), T4(50mg/kg), T5(70mg/kg), and T6(100mg/kg) were commercial feed supplemented with respective concentration of powdered Yucca shidigera saponin for experiment A in both starter and finisher diets. Throughout 42 days of rearing, birds were weighed weekly for the determination of feed conversion ratio, while the mortality and abnormal clinical sign were recorded daily. A total of 60 broilers were selected for starter and finisher phase sampling, one from each replicate in each dietary treatment at random. Samples were slaughter for leucocyte profiling analysis, organ measurement, blood biomarkers, and telomere length analysis. The same experimental design was conducted for another two more studies using dried Brachiaria decumbens grass as experiment B and saponins extract from Brachiaria decumbens grass as experiment C. As for the result, T6(100mg/kg) broilers supplemented with Y. schidigera saponins, experiment (A); T3(25mg/kg) broilers supplemented of B. decumbens, experiment (B); and T6(100mg/kg) broilers supplemented B. decumbens saponins extract, experiment (C) elucidated significantly better (P<0.05) growth performance, higher white blood cell count, higher blood biomarkers, and longer telomere length expression during the finisher phase as compared to the other treatments. Those treatments showed a superior growth performance with the highest body weight and body weight gain leading to the best FCR. However, there were no notable clinical signs observed with a low mortality rate among all treatments. In addition, there was no significant difference (P>0.05) observed in the organ morphometric among different treatments. On the other hand, T6(100mg/kg) from experiments A and C, whereas T3(25mg/kg) from experiment B showed better expression of total white blood cell count, and lower heterophil and lymphocyte ratio indicating a better health performance. This was supported by the higher concentration of immunoglobulin A, immunoglobulin G, immunoglobulin M and antibody-related cytokines; interleukin-4 and interleukin-7. Besides, the telomere length analysis of broilers from experiments A, B, and C respectively exhibited longer telomere length expression as compared to the other treatments. In summary, commercial broilers supplemented with 100 mg/kg of Y. schidigera saponins, 25 mg/kg of B. decumbens grass, and 100 mg/kg B. decumbens saponins extract demonstrated better results of growth performance, higher WBC total count, higher blood biomarkers, and better telomere length expression. 100 mg/kg of B. decumbens saponins extract was the best candidate comparing to all treatments in each experiment and this shows pure B. decumbens saponins extract supplementation was strongly advised be the best option as a secure natural additive that may enhanced the health and production of broilers. This can be used in the broiler industry as an antibiotic replacer, which ultimately prevents antibiotic resistance as well as increases the food safety of broiler products.